2021
DOI: 10.1155/2021/8671384
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Chitosan as an Eco-Friendly Binder for High-Performance Wood-Based Fiberboard

Abstract: High-performance wood-based fiberboards with high strength and dimensional stability were fabricated by hot-pressing method using 2,5-dimethoxy-2,5-dihydrofuran (DHF) cross-linked chitosan (CS) as an eco-friendly binder. The effects of cross-linked chitosan on the mechanical properties and dimensional stability of wood-based fiberboards were investigated. It is evident that cross-linked chitosan addition was effective in improving mechanical properties and dimensional stability of wood-based fiberboards. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The utilization of lignin is expected to ensure efficient reactivity by providing abundant phenolic hydroxyl groups and free aromatic C3 or C5 position, as well as the ability to undergo hydroxymethylation and polymerization by condensation with formaldehyde (Rodrigues et al 2023). In addition, biological-based compounds used as impregnants have included by-products of biological activity, such as chitosan from crustacean shells (Larnøy et al 2005;Huang et al 2021), propolis extract produced by Apis mellifera (Woźniak et al 2020), and beeswax. There is also a possible variation between those compounds due to differences in species of biological organisms, source of food especially for propolis and beeswax, and extraction method.…”
Section: Development Of Environment-friendly Impregnating Agentsmentioning
confidence: 99%
“…The utilization of lignin is expected to ensure efficient reactivity by providing abundant phenolic hydroxyl groups and free aromatic C3 or C5 position, as well as the ability to undergo hydroxymethylation and polymerization by condensation with formaldehyde (Rodrigues et al 2023). In addition, biological-based compounds used as impregnants have included by-products of biological activity, such as chitosan from crustacean shells (Larnøy et al 2005;Huang et al 2021), propolis extract produced by Apis mellifera (Woźniak et al 2020), and beeswax. There is also a possible variation between those compounds due to differences in species of biological organisms, source of food especially for propolis and beeswax, and extraction method.…”
Section: Development Of Environment-friendly Impregnating Agentsmentioning
confidence: 99%
“…However, the poor mechanical properties of the chitosan linear structure limit the expansion of its application. In order to overcome this defect, a stable three-dimensional network structure is formed by chemical crosslinking [13,14]. JI et al [15] prepared a lignosulfonate/chitosan-based adhesive by making use of glutaraldehyde as a crosslinking agent.…”
Section: Introductionmentioning
confidence: 99%
“…Through the mechanical property test, results showed that the MDF prepared with the mass ratio of glutaraldehyde/chitosan between 0.25~0.75 met China's MDF national standard. Huang et al [14] utilized 2, 5-dimethoxy-2, 5-dihydrofuran-crosslinked CS as an environmentally-friendly binder to prepare environmentally-friendly mediumdensity fiberboard through the hot-pressing method. The results indicated that crosslinked chitosan could effectively improve the mechanical properties and dimensional stability of wood-based panels.…”
Section: Introductionmentioning
confidence: 99%